In Vivo PET Imaging of the Activated Immune Environment in a Small Animal Model of Inflammatory Arthritis - Benjamin L. Franc MD, MS; Sam Goth PhD; John MacKenzie MD; Xiaojuan Li PhD; Joseph Blecha MS; Tina Lam MS; Salma Jivan BS; Randall A. Hawkins MD, PhD; Henry VanBrocklin PhD (Molecular Imaging)
Background: Evolving immune-mediated therapeutic strategies for rheumatoid arthritis (RA) may benefit from an improved understanding of the complex role that T-cell activation plays in RA. This study assessed the potential of fluorine-18-labeled 9-β- d -arabinofuranosylguanine ([ 18 F]F-AraG) positron emission tomography (PET) imaging to report immune activation in vivo in an adjuvant-induced arthritis (AIA) small animal model. Methods: Using positron emission tomography–computed tomography imaging, uptake of [ 18 F]F-AraG in the paws of mice affected by arthritis at 6 (acute) and 20 (chronic) days following AIA induction in a single paw was assessed and compared to uptake in contralateral control paws. Fractions of T cells and B cells demonstrating markers of activation at the 2 time points were determined by flow cytometry. Results: Differential uptake of [ 18 F]F-AraG was demonstrated on imaging of the affected joint when compared to control at both acute and chronic time points with corresponding changes in markers of T-cell activation observed on flow cytometry. Conclusion: [ 18 F]F-AraG may serve as an imaging biomarker of T-cell activation in inflammatory arthritis. Further development of this technique is warranted and could offer a tool to explore the temporal link between activated T cells and RA as well as to monitor immune-mediated therapies for RA in clinical trials.